English English - Qur'ani, Balqis Nazilia; Cholidatul Ulfa Ulumiyah; Nafis Wardani (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2024)
English learning in Indonesia still has various problems, namely English is still as a foreign language where the pronunciation and pronunciation methods are quite difficult, so many students feel difficult to pronounce English words. The difficulties caused the students were not interested in learning pronunciation. The purpose of this study was to improve students' pronunciation skills using word pattern strategy because this strategy was an effective strategy to increase students’ pronunciation in MI Alhidayah. This study used classroom action research which consisted of four stages: planning, action, observation, and reflection. The data were obtained from research observations taken from third grade consisting of 24 students. The results showed that pre-test data was the average of 56 and the average of post-test was 78. The conclusion of this study was that using word pattern strategy improved pronunciation skills in third grade students of MI Al-Hidayah. Learning pronunciation frequently by using word patterns, students develop sensitivity to English sounds and intonation.